Adult Romantic Attachment in Early Adults with Divorced Parents (Phenomenological Study of Members of the Young Professional Cell Community at Kemah Daud Church, Yogyakarta) - Prastiwi, Ira; Harahap, Dewi Handayani; Rahma, Izzah Annisatur (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Parental divorce can disrupt children's psychosocial development, especially in forming a strong sense of confidence, emotional stability and identity. The impact of unresolved conflict at this stage will be seen in the Intimacy vs. Isolation stage, namely in early adulthood. This study aims to understand the description of adult romantic attachment in early adult individuals from divorced parents. This study uses a phenomenological approach that allows researchers to understand the dynamics of the subject. The results of this study indicate that there is a picture of adult romantic attachment in early adults with divorced parents. Subjects who have strong trust in themselves and their partners tend to have better openness, emotional involvement, and relationship satisfaction. In contrast, individuals who have low self-confidence or distrust of partners tend to face challenges in building healthy and satisfying relationships. The implications of this study show the importance of knowing their attachment picture and being able to build healthier relationships in the future. Perceraian orang tua dapat mengganggu perkembangan psikososial anak, khususnya dalam membentuk rasa percaya diri, stabilitas emosi, dan identitas yang kuat. Dampak dari konflik yang tidak terselesaikan pada tahap ini akan terlihat di tahap Intimacy vs. Isolation yaitu pada usia dewasa awal. Penelitian ini bertujuan untuk memahami gambaran adult romantic attachment pada individu dewasa awal dari orang tua yang bercerai. Penelitian ini menggunakan pendekatan fenomenologi yang memungkinkan peneliti memahami dinamika subjek. Hasil penelitian ini menunjukkan bahwa terdapat gambaran dari adult romantic attachment pada dewasa awal dengan orang tua bercerai. Subjek yang memiliki kepercayaan yang kuat terhadap diri sendiri maupun pasangan cenderung memiliki keterbukaan, keterlibatan emosional, dan kepuasan hubungan yang lebih baik. Sebaliknya, individu yang memiliki kepercayaan diri rendah atau ketidakpercayaan terhadap pasangan cenderung menghadapi tantangan dalam membangun hubungan yang sehat dan memuaskan. Implikasi penelitian ini menunjukkan pentingnya mengetahui gambaran kelekatan mereka dan mampu membangun hubungan yang lebih sehat di masa depan.